Increasing the confidence and knowledge of occupational therapy and physiotherapy students when communicating with people with aphasia: A pre–post intervention study. (September 2015) - Cameron, Ashley; McPhail, Steven M.; Hudson, Kyla; Fleming, Jennifer; Lethlean, Jennifer; Finch, Emma
<x content-type="archive" xml:space="preserve">Abstract</x> This study investigated occupational therapy and physiotherapy students' level of confidence and knowledge of strategies for communicating with people with aphasia (PWA) before and after a communication partner-training (CPT) program. Twenty-eight physiotherapy and occupational therapy students participated in a pre–post CPT program. Students completed a customized mixed-methods questionnaire before and after the intervention. The CPT program involved a lecture about effective communication strategies followed by a conversation with PWA to practice strategies learnt. Before CPT, students were not confident with the possibility of communicating with PWA. Students demonstrated rudimentary knowledge of supported conversation, identifying a maximum of five strategies for communicating effectively with PWA. Following intervention, students demonstrated increased confidence. Students' knowledge of effective communication strategies improved, with students identifying a maximum of 16 suitable strategies post-training. The results suggest that occupational therapy and physiotherapy students have potential to benefit from practical training in supported communication with PWA, which may assist them during placements in clinical settings with neurological patients or subsequent employment.